The Role of Cooperative Culture in Shaping the Saving Behavior of Members of the Kopdit Suru Pudi Koting Savings and Loan Cooperative - Benedikta Merciana Rada; Wilhelmina Mitan; Paulus Libu Lamawitak (Neo Journal of economy and social humanities, 2026)
This study analyzes the influence of cooperative culture on members’ saving behavior at KSP Kopdit Suru Pudi Koting. The Research aims to describe the role of organizational values in shaping consistent saving habits and to identify the determinants of members’ intention to save. The analysis method used is a qualitative descriptive approach based on the Theory of Planned Behavior (TPB). The study's results show that a culture of cooperation and kinship functions as a dominant subjective norm, motivating members to save. However, the effectiveness of this behavior is limited by low behavioral control due to fluctuations in members’ income. Although the integration of the SIKOPDIT system and service quality has been optimal, it is necessary to strengthen education on cultural values to transform saving behavior from a mere administrative obligation into a sustainable internal awareness.